Pengelolaan Arsip Vital pada Kantor Arsip Universitas Indonesia - Lasambouw, Irma Fajriani; Kurniasih, Novi (Utilitas, 2016)
Based on the results of research, the transfer of vital archives is based on the University Rectors Decision Letter and the activities of transfer is the identification of vital archives and the classification of vital archives by the archivist team. The recording of vital archives is referring to Norms, Standard Procedures and Criteria (NSPK) Filing and Archive Retention Schedule (JRA). The Office of Archives also carries out the work ethic of the employee and the making of the archivists work targets to make the listing activity more effective and efficient. Digitalization is for the rediscovery of archives, as a form of archive rescue method as well as archive publication. Preservation of vital archives at the Archives Office of the University of Indonesia covers the storage, maintenance and restoration of vital archives.The vital archive storage in the archives office refers to the NSPK and POB Archives as well as to the ANRI Regulation No. 49 of 2015 on the procedures of the vital archive program. They are who maintaining the vital archives is the assigned archivist in particular and all employees in general. Recovery of archives at the University of Indonesia archives has not been done before, because there is no vital archive that requires special recovery. In securing the archives, the manager gets limited access authority according to the field of work unit. The technology applied in the archive office in performing archival safeguards refers to the System Technology and Information Technology Standards. Good technology is required in the archives of the University of Indonesia to ensure the maintenance of thearchive by supporting secure accessibility.